Opinion 2486: Opinion 2486 (Case 3506) – Allosaurus Marsh, 1877 (Dinosauria, Theropoda): usage conserved by designation of a neotype for its type species Allosaurus fragilis Marsh, 1877 (Bulletin of Zoological Nomenclature, 2023)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the  usage of the name Allosaurus Marsh, 1877, by designating specimen USNM 4734 as the neotype to replace  the nondiagnostic holotype (YPM 1930) of Allosaurus fragilis Marsh, 1877. In their comment supporting Case 3506, Loewen & Chure (2010) specified the skeletal elements (attributable to a single individual) that should  constitute the neotype.
Keywords: Nomenclature; taxonomy; Dinosauria; Theropoda; Allosaurus; Allosaurus fragilis; dinosaur; Jurassic; North America; Europe